Reproductive Cycle of Grey Mullets (Mugilidae) and Their Relationships with Seasonal Environmental Changes, in Libyan Coastal Waters: A Scoping Review with Environmental Data Insights - Najiyah Amdawi, (AlQalam Journal of Medical and Applied Sciences, 2025)
Mugilids (Mugilidae) are among the most valuable commercial fishes in the Mediterranean, particularly Mugil cephalus and Chelon ramada. Because the reproductive biology of these species is highly sensitive to small changes in environmental conditions, they are ideal organisms for evaluating the coupling of biology and ecosystem dynamics. This study provides a scoping review of the reproductive cycle of mullets in the Libyan territorial waters and connects species reproductive characteristics with remote environmental variables such as sea surface temperature (SST) and chlorophyll a concentration (Chl-a). To assess the connection between seasonal gonadal maturation, spawning peaks, and derived reproductive indices, 21 relevant papers published between 2006 and 2025 were reviewed. Results suggest that spawning typically occurs in late summer to early autumn, corresponding to periods of higher SST and lower Chl-a. A comparative analysis of adjacent Mediterranean areas confirms that environmental signals control both the timing and the strength of mullet reproduction. The findings highlight the need for continuous ecological monitoring of Libyan waters, and the insights obtained could inform ecologically based fishery management policies aimed at establishing sustainable closed seasons that adapt to climatic changes.